Morfologia e anatomia das domácias em Coffea arabica L. - Barros, Myrthes Apparecida Adâmoli de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
The morphology and anatomy of domatia structures of 21 varieties and 4 strains of coffee plants (Coffea arabica L.) were studied and the resultas may be summarized as follows: 1. All the domatia structures observed belongs to type b of CHEVALIER. 2. In all coffee plants studied the domatia structures have the same tópographic position: close to the primary vein, between this and the secondary veins. 3. In each leaf the domatiae are distributed from the base up to 2/3 of the midrib length. 4. Differences in structure occur among the epidermis that lined the mouth opening, channel and chamber. No stomata were found here. 5. Te morphological and anatomical variations found in the domatia structures are not enough to distinguish apart the several coffee plant varietis studied.